1996
DOI: 10.1182/blood.v88.10.3731.bloodjournal88103731
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and function of human hematopoietic cells engrafting immune- deficient CB17-severe combined immunodeficiency mice and nonobese diabetic-severe combined immunodeficiency mice after transplantation of human cord blood mononuclear cells

Abstract: In an attempt to understand better the regulation of stem cell function in chimeric immunodeficient mice transplanted with human cells, and the filiation between progenitor cells identified in vitro and in vivo, we assessed the different compartments of hematopoietic progenitors found in the marrow of CB17-severe combined immunodeficiency (SCID) mice (34 mice, 9 experiments) after intravenous injection of 2 to 3 x 10(7) cord blood mononuclear cells. On average 6.3 +/-4 x 10(5) human cells were detected per fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(75 citation statements)
references
References 30 publications
2
71
0
2
Order By: Relevance
“…Our estimates of the proportion of LTC-IC in CB using the LTC-IC readout suggest that, on average, 32/10 5 MNC or 43/10 3 CD34 + cells in CB are LTC-IC. These compare favorably with reported frequencies of 59/10 5 MNCs [27], 23/10 5 MNCs [28], and 71/10 3 CB CD34 + cells [29] using the LTC-IC readout after culture on normal bone marrow stroma feeder layers. The CAFC readout, although popular, seems to be fraught with problems.…”
Section: Discussionsupporting
confidence: 87%
“…Our estimates of the proportion of LTC-IC in CB using the LTC-IC readout suggest that, on average, 32/10 5 MNC or 43/10 3 CD34 + cells in CB are LTC-IC. These compare favorably with reported frequencies of 59/10 5 MNCs [27], 23/10 5 MNCs [28], and 71/10 3 CB CD34 + cells [29] using the LTC-IC readout after culture on normal bone marrow stroma feeder layers. The CAFC readout, although popular, seems to be fraught with problems.…”
Section: Discussionsupporting
confidence: 87%
“…The discovery a few years ago that intravenously injected normal human haemopoietic cells can home into the marrow space of sublethally irradiated immunodeficient mice and remain viable there for many months opened a new era of investigation of the in vivo reconstituting properties of various types of human transplants (Dick, 1996). Recent studies using NOD/SCID mice as recipients (Larochelle et al, 1995(Larochelle et al, , 1996Pflumio et al, 1996;Lowry et al, 1996;Cashman et al, 1997) indicate the superiority of this latter model and suggest that it will be useful for addressing many outstanding questions about human haemopoietic stem cells with in vivo repopulating activity. One issue of current interest is the stem cell content and in vivo repopulating potential of human cord blood cells by comparison to adult marrow cells.…”
Section: Discussionmentioning
confidence: 99%
“…bone or fetal liver) previously implanted into mice with the severe combined immunodeficiency (SCID) mutation (the so-called SCID-hu mouse model) (McCune et al, 1988;Kyoizumi et al, 1992;Fraser et al, 1995), and by simple intravenous injection of various types of myeloablated immunodeficient mice (e.g. SCID mice, BEIGE-NUDE-Xid mice [bnx mice], and nonobese-diabetic-SCID [NOD/SCID] mice) (Kamel-Reid & Dick, 1988;Lapidot et al, 1992;Nolta et al, 1994;Lowry et al, 1996;Pflumio et al, 1996;Larochelle et al, 1996;Cashman et al, 1997). These latter studies have shown that conditions prevailing within the marrow microenvironment of several species, including mice, are able to sustain many aspects of human haemopoiesis in spite of the known species-restricted activity of some of the molecules used to stimulate these cells in vitro.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The initial report on the increased engraftment of human stem cells in NOD-scid mice was rapidly confirmed in a number of laboratories [105][106][107]. The enhanced ability of NODscid mice to support human stem cell engraftment was further demonstrated by comparing the levels of human cell engraftment to those observed in BALB/c-scid mice expressing transgenes for SCF, IL-3, and GM-CSF [77].…”
Section: Characteristics Of Stem Cells That Repopulate Nod-scid Micementioning
confidence: 95%